CES employment recovers in 2014. - Mullins, John P.; Forbes, Brittney E. (Monthly Labor Review, 2015)
U.S. nonfarm payroll employment continued to grow steadily in 2014, adding 3.1 million jobs, according to the Current Employment Statistics (CES) survey. This article uses CES data to discuss how private and public industry employment, hours, and earnings changed over the year. Job gains in 2014 were widespread across industries, with all broad industry groups experiencing employment increases. Employment growth was concentrated in the service-providing sector and led by industries that have been adding jobs for some time. However, even goods-producing industries saw an uptick in employment growth over the year.